2011
DOI: 10.1002/pad.589
|View full text |Cite
|
Sign up to set email alerts
|

Public–private partnership in labor standards governance: Better factories Cambodia

Abstract: The growth of outsourcing in apparel manufacturing has raised concerns about increasingly exploitative working conditions. Given the failure of existing enforcement mechanisms, we need to look to alternate institutional structures to address the global challenge of declining labor standards. This paper examines the case of Better Factories Cambodia (BFC), a public–private partnership (PPP) that has effectively protected workers' rights through collaboration between the Government of Cambodia, the International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Bhuiyan (2010) has observed that failure to observe good governance and politico-administrative culture of a country may cause alternative forms of governance like PPPs to be established in service delivery sectors. Researchers tend to agree that governance and network theories and their various dimensions are helpful in understanding PPP setting, implementation and outcomes (Aars & Fimreite, 2005;Andon, 2012;da Cruz & Marques, 2012;Lippi et al, 2008;Mauldin, 2012;Parola et al, 2013;van den Hurk & Verhoest, 2015;van der Heijden, 2013;Velotti et al, 2012;Wetterberg, 2011).…”
Section: Theories/perspectives Of Ppp Effectivenessmentioning
confidence: 99%
“…Bhuiyan (2010) has observed that failure to observe good governance and politico-administrative culture of a country may cause alternative forms of governance like PPPs to be established in service delivery sectors. Researchers tend to agree that governance and network theories and their various dimensions are helpful in understanding PPP setting, implementation and outcomes (Aars & Fimreite, 2005;Andon, 2012;da Cruz & Marques, 2012;Lippi et al, 2008;Mauldin, 2012;Parola et al, 2013;van den Hurk & Verhoest, 2015;van der Heijden, 2013;Velotti et al, 2012;Wetterberg, 2011).…”
Section: Theories/perspectives Of Ppp Effectivenessmentioning
confidence: 99%
“…Social labeling initiatives are just one example of the kind of system that emerges in the absence of effective enforcement. Wetterberg (2011), for example, focuses on the rise of the Better Factories Cambodia program in the context of insufficient enforcement. This paper, in particular, describes how the Better Factories Cambodia approach took the lack of enforcement into account to forge an alternative multistakeholder approach that has been discussed earlier in this review.…”
Section: Box 3: India's Labor Reformsmentioning
confidence: 99%
“…This is a contract between governments, international organisations, companies, non-governmental organisations, investors, business and industrial organisations to increase transparency, avoid corruption and improve governance in transactions between governments and companies in the extractive industries (Aaronson, 2011). The Government of Cambodia, for example, has effectively protected workers' rights through collaboration between the International Labour Organisation and multinational firms through Better Factories Cambodia (BFC) (Wetterberg, 2011).…”
Section: Ethical Standardsmentioning
confidence: 99%